Avoiding Stffness: Perspectives of agile technology diffusion - Ezcan, Volkan; Goulding, Jack Steven; Pour Rahimian Leilabadi, Farzad; Kuruoglu, Murat (My University, 2015)
The increased pervasiveness of Information and Communication Technology (ICT) within the Architecture Engineering and Construction (AEC) sector, not only introduces unparalleled opportunities for enhancing the performance of design/engineering/construction processes per se, but also serves as a unique lever for improving and delivering overall competitiveness. However, whilst the onset and evolution of ICT keeps improving, it is also recognised that organisations often fail to match this evolution, most notably through the adoption, diffusion and dissemination of this technology. This has also been acknowledged as a barrier, particularly concerning innovation opportunities. Cognisant of this, organisations are increasingly looking to secure full advantage of emerging ICT developments. On this theme, this study identifies a series of priority areas for organisations, with the specific remit of securing agility (in the market) through ICT diffusion. A questionnaire, based on an Agile-Technology Diffusion framework, was used to capture the perceptions of management professionals working in the Turkish AEC sector. The ranking analysis of the survey results and comparison of the different management perceptions (levels) are presented for discussion. Research findings identify several priority areas that need to be addressed. These findings also uncover significant differences in the perceptions of different management levels - which can help decision makers appreciate the holistic interdependencies, especially the factors which impinge (or impede) overall competitiveness.
Keywords: W200